Liberated Threads : Black Women, Style, and the Global Politics of Soul - Ford, Tanisha C. (Book collections on Project MUSE., 2015)
From the civil rights and Black Power era of the 1960s through antiapartheid activism in the 1980s and beyond, black women have used their clothing, hair, and style not simply as a fashion statement but as a powerful tool of resistance. Whether using stiletto heels as weapons to protect against police attacks or incorporating African-themed designs into everyday wear, these fashion-forward women celebrated their identities and pushed for equality. In this thought-provoking book, Tanisha C. Ford explores how and why black women in places as far-flung as New York City, Atlanta, London, and Johannesburg incorporated style and beauty culture into their activism. Focusing on the emergence of the "soul style" movement--represented in clothing, jewelry, hairstyles, and more--Liberated Threads shows that black women's fashion choices became galvanizing symbols of gender and political liberation. Drawing from an eclectic archive, Ford offers a new way of studying how black style and Soul Power moved beyond national boundaries, sparking a global fashion phenomenon. Following celebrities, models, college students, and everyday women as they moved through fashion boutiques, beauty salons, and record stores, Ford narrates the fascinating intertwining histories of Black Freedom and fashion.